Energy Adequacy, Body Composition, and Menstrual Cycle Disorder: A Correlation Study on Medical and Midwifery Students - Siti Aria Rahmani Novianto; Bambang Purwanto; Budi Prasetyo (Universitas Airlangga, 2023)
Highlights:1. Menstrual cycle disturbance is related to organic and non-organic factors.2. BMI, waist circumference, and energy adequacy did not have a significant correlation with menstrual cycle frequencies among medical students. AbstractIntroduction: Menstrual cycle disturbance is related to irregular reproductive hormones, which are influenced by organic and non-organic factors. This study aimed to determine the correlation between energy adequacy, body composition, and menstrual cycle disorder. Methods: This was an observational analytic study with a case-control design. The population of this study was medical and midwifery students in the Faculty of Medicine, Universitas Airlangga, Surabaya. 72 subjects consisted of 36 women with a normal menstrual cycle between 24–38 days and 36 women with a menstrual cycle length of <24 days or >38 days. Data about body composition, energy adequacy, and menstrual cycle were all collected by questionnaire. Data were analyzed by Spearman and Continency Coefficient correlation.Results: Most participants (66.7%) had normal body mass index (BMI), while 19.4% were overweight. Meanwhile, waist circumference in 63.9% of subjects was categorized as not obese. The participants' physical activities ranged from sedentary to vigorous (0 to 7386 MET-minutes/week). Less than one-third of the participants (27.8%) had an energy balance, while in most subjects (56.9%), energy adequacy was classified as deficit or negative energy balance. The statistics showed a p-value >0.05 in BMI (p = 0.231), waist circumference (p = 0.141), and energy adequacy (p = 0.389) with the menstrual cycle, indicating no correlation between BMI, energy adequacy, and waist circumference with menstrual cycle frequencies.Conclusion: Statistical analysis showed no correlation between energy adequacy, BMI, and waist circumference with menstrual cycle frequency disorder in students in the Faculty of Medicine, Universitas Airlangga, Surabaya.